Hi, I need help with these. Simplfy as much as possible. ((3x2^n+1) + (5x2^n)) / ((7x2^n) - (3x2^n-1)) solve for x 2y-1/1-x = 2y+1 x not =1 , y not =-1/2 solve for s 2s - 2/s = 3 s not = 0
Follow Math Help Forum on Facebook and Google+
Originally Posted by tim_mannire Hi, I need help with these. Simplfy as much as possible. ((3x2^n+1) + (5x2^n)) / ((7x2^n) - (3x2^n-1)) solve for x 2y-1/1-x = 2y+1 x not =1 , y not =-1/2 solve for s 2s - 2/s = 3 s not = 0 ((3x is apart of the equation below.. i dont know y it isolated itself like that!
Wrong form but here is what you are looking for if this is the equation you mean Factor out a and Obtain the same common denominator and
View Tag Cloud